2017
DOI: 10.1038/srep43547
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant response is a protective mechanism against nutrient deprivation in C. elegans

Abstract: Animals often experience periods of nutrient deprivation; however, the molecular mechanisms by which animals survive starvation remain largely unknown. In the nematode Caenorhabditis elegans, the nuclear receptor DAF-12 acts as a dietary and environmental sensor to orchestrate diverse aspects of development, metabolism, and reproduction. Recently, we have reported that DAF-12 together with co-repressor DIN-1S is required for starvation tolerance by promoting fat mobilization. In this report, we found that gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…These genes account for 26% of all annotated down-regulated transcripts in our differential expression analyses. In Blaberus discoidalis CYP450-4C1 is involved in fatty acid oxidation during starvation to synthesize trehalose, the main circulating carbohydrate of insects, but is not needed for vitellogenin synthesis, which is up-regulated under high-feeding conditions (5759). In summary, ~100 differentially expressed genes were identified in IP-KD ants, many of which can be linked to various metabolic processes, such as fat, protein, and DNA metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…These genes account for 26% of all annotated down-regulated transcripts in our differential expression analyses. In Blaberus discoidalis CYP450-4C1 is involved in fatty acid oxidation during starvation to synthesize trehalose, the main circulating carbohydrate of insects, but is not needed for vitellogenin synthesis, which is up-regulated under high-feeding conditions (5759). In summary, ~100 differentially expressed genes were identified in IP-KD ants, many of which can be linked to various metabolic processes, such as fat, protein, and DNA metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The gst-4 gene encodes a glutathione-s-transferase, and is a target for the ROS responsive transcriptional regulator SKN-1( C . elegans Nrf2 ortholog) [ 86 , 87 ]. As shown in Fig 7B and 7C , tm5915 animals demonstrate a significant elevation in P gst-4 ::GFP expression.…”
Section: Resultsmentioning
confidence: 99%
“…To determine levels of stress we used the transcriptional reporter strains, dvIs19 [ p gst-4 :GFP] and zcIs4 [ p hsp-4 :GFP] to measure oxidative stress and ER stress respectively. We adapted previously described methods [ 87 , 88 ]. Briefly, the overall p gst-4 :GFP fluorescence intensity/μm per 15–20 3 day adult swip-10 animals and 15–20 3 day adult N2 animals (with subtracted background fluorescence per animal) was determined, and the fold change GFP intensity compared to N2 signal was calculated for all animals assayed from one population and subsequently averaged over 4 independent days (n = 60–75 animals assayed).…”
Section: Methodsmentioning
confidence: 99%
“…GST activity was severely reduced by starvation, while subsequent refeeding induced an even greater decrease in the intestine of Acipenser stellatus juveniles. It was reported that starvation usually enhances the innate enzymatic capacity of detoxification by up-regulating the expression of genes that are related to antioxidant mechanisms, especially GST [ 50 ]. In starved individuals, GPx activity was highly increased compared to constantly fed ones and GSH reserves might have been used with priority as cofactor for GPx than for GST enzyme during starvation.…”
Section: Discussionmentioning
confidence: 99%